Trajectories across the healthy adult lifespan on sense of direction, spatial anxiety, and attitude in exploring places - Muffato, Veronica; Miola, Laura; Pazzaglia, Francesca; Meneghetti, Chiara (Frontiers in Psychology, 2023)
Introduction: Self-evaluations about orientation and navigation in the environment contribute to individual differences in spatial cognition. Evidence suggests they may change, even slightly, with the progression of adulthood. It is necessary to improve the framing of environment-related subjective selfevaluations in adulthood and aging by examining how they change and the factors related to them. Therefore, the current study aims to examine the developmental trajectories of sense of direction, spatial anxiety and attitude in exploring place across the adult lifespan while also considering gender and education. Materials and methods: A sample of 1,946 participants (1,068 women), aged 18-87, completed the sense of direction and spatial representation, spatial anxiety and attitudes in exploring scales. Results: The regression models showed a linear increase in sense of direction with age, stable spatial anxiety until age 66 when anxiety began increasing, and a stable attitude in exploring with a deflection by age 71. Gender played a role in all three types of self-evaluations, with men reporting higher ratings in sense of direction and attitudes in exploring (especially in older men), and lower levels of spatial anxiety than women did. Education also played a role, with higher education years associated with lower ratings in spatial anxiety and a higher sense of direction, nullifying gender differences in the latter. Discussion: These results offer, in the spatial cognition framework, a better understanding of how specific environment-related self-evaluations develop with age and related factors, such as education. This underscores the importance of enhancing them, in women and older adults.